Perlindungan Hak Kelompok Rentan di Indonesia: Analisis Kebijakan terhadap Disabilitas, Anak, dan Minoritas Agama - Herlina Anut; Karolus Liat Lengo; Melkian Diki Talumbani; Maria Galgani Rovianyta Toi; Fadil Mas'ud (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the national and regional legal frameworks governing the protection of vulnerable groups in Indonesia, including persons with disabilities, children, and religious and ethnic minorities, while evaluating the effectiveness of their implementation in ensuring equal rights and social justice. The research employs a qualitative approach through a literature study, utilizing legal documents, academic literature, official reports, and scholarly publications related to the protection of vulnerable groups. The analysis reveals that Indonesia has established a strong legal foundation, including the 1945 Constitution, Law No. 8 of 2016 on Persons with Disabilities, Law No. 35 of 2014 on Child Protection, and commitments to international instruments such as the CRPD and CRC. Nevertheless, policy implementation still faces significant challenges, including limited inter-agency coordination, resource constraints, social stigma, and low public awareness. This study emphasizes the need to strengthen institutional capacity, reform policies, promote public education, and enhance cross-sector collaboration to ensure inclusive and equitable protection for vulnerable groups, in line with the principles of Pancasila and the Sustainable Development Goals (SDGs).